2017
DOI: 10.3390/ma10060639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Carbon Sources on Bacterial Nanocellulose Production and Structure Using the Low pH Resistant Strain Komagataeibacter Medellinensis

Abstract: Bacterial cellulose (BC) is a polymer obtained by fermentation with microorganism of different genera. Recently, new producer species have been discovered, which require identification of the most important variables affecting cellulose production. In this work, the influence of different carbon sources in BC production by a novel low pH-resistant strain Komagataeibacter medellinensis was established. The Hestrin-Schramm culture medium was used as a reference and was compared to other media comprising glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 44 publications
12
59
2
2
Order By: Relevance
“…In Figure 1 at 72 h starts deceleration of cell growth that is in line to results in static conditions obtained by Molina-Ramírez et al (Molina-Ramírez et al 2017) and agitated conditions obtained by Yoshinaga, Tonouchi, Watanabe (Yoshinaga et al 1997) and Okiyama, Shirae, Kano, Yamanaka (Okiyama et al 1992) with an strain belong to Komagataeibacter genus. These results suggest that fermentation mode (static or agitated) did not affect growth profile, but agitated mode allows obtain a higher cell density yield compared to static mode, in agitated mode a biomass measured by was 1.091(OD 600 ) against 0.690 (OD 600 ) obtained in static fermentation mode (data not shown).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In Figure 1 at 72 h starts deceleration of cell growth that is in line to results in static conditions obtained by Molina-Ramírez et al (Molina-Ramírez et al 2017) and agitated conditions obtained by Yoshinaga, Tonouchi, Watanabe (Yoshinaga et al 1997) and Okiyama, Shirae, Kano, Yamanaka (Okiyama et al 1992) with an strain belong to Komagataeibacter genus. These results suggest that fermentation mode (static or agitated) did not affect growth profile, but agitated mode allows obtain a higher cell density yield compared to static mode, in agitated mode a biomass measured by was 1.091(OD 600 ) against 0.690 (OD 600 ) obtained in static fermentation mode (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…These results suggest that fermentation mode (static or agitated) did not affect growth profile, but agitated mode allows obtain a higher cell density yield compared to static mode, in agitated mode a biomass measured by was 1.091(OD 600 ) against 0.690 (OD 600 ) obtained in static fermentation mode (data not shown). As was mentioned above, 72 h is the age where the K. medellinensis NBRC 3288 begins deceleration stage and match with begins of BC production according to Molina-Ramírez et al (Molina-Ramírez et al 2017), these results suggest that an inoculum of 72 h, would be the most appropriate to use in the further BC production process (Chao et al 2000; Bae and Shoda 2004). Likewise, Table 2 shows the results of maximum growth rate (μ m , h −1 ) in each treatment evaluated and as it was expected, the highest mm was obtained in the treatment with the highest biomass, which granted that culture medium of treatment 7 is the best to improve cell density yield of K. medellinensis NBRC 3288.…”
Section: Discussionsupporting
confidence: 57%
“…The diffraction peaks were fitted using pseudo‐Voigt and Gaussian functions. The crystallinity index (Cr.I) was calculated according to Molina‐Ramirez et al as the percentage of the area of all crystalline peaks to the total area . The d‐spacing (d) between the crystal planes was determined using Bragg's law expressed by Eq.…”
Section: Methodsmentioning
confidence: 99%
“…D-Glucose, ethanol, D-fructose, maltose, sucrose, sorbitol, D-mannitol, D-ribose and D-xylose were reported as suitable carbon sources for this strain [26]. The cellulose producing ability of this strain has been assessed on different occasions [22,37,38]. However, reports on BNC production and the optimal conditions were not consistent, possibly due to the differing fermentation conditions, thus we have carried out the optimization study, using reported parameters as a starting point.…”
Section: Optimisation Of Bnc Productionmentioning
confidence: 99%